الضوابط القانونية لحماية الطفل من الإشهار التلفزيوني في الجزائر - بلقاسم,سميحة; بوشوشه,حميد (University of Eloued جامعة الوادي, 2024)
يُشكّل الإشهار التلفزيوني أداة قوية للتأثير في المتلقّين لمختلف المضامين والرسائل الإشهارية وتوجيه سلوكياتهم، والطفل باعتباره شريحة هامة من المجتمع ويعتبر محور القرارات الشرائية للآباء، وهدفا تسويقيا وجزءً هامّا من السوق بالنظر للتأثير الذي يحدثه الإشهار التلفزيوني على تفضيلاته وتشكيل اهتماماته وسلوكياته، فقد لجأ المعلنون وأصحاب المؤسسات الإشهارية لاستغلال هذا الجانب لتحقيق مكاسب تجارية من خلال استخدام الطفل في الحملات الإشهارية دون مراعاة خصوصيته وقدرته المحدودة على تقييم المحتوى الإشهاري الذي يتعرّض له أو الذي يشارك في الترويج له، مما يثير الكثير من المخاوف حول طبيعة هذه الممارسات من الناحية القانونية، إذ تستعرض هذه الدراسة الجوانب القانونية المرتبطة بهذا الموضوع من خلال قراءة في النصوص والتنظيمات الخاصة بقطاع الإشهار وقوانين الإعلام في الجزائر، بهدف الكشف عن الحماية القانونية التي يكفلها التشريع الجزائري للطفل من الإشهار التلفزيوني، وقد توصلت هذه الورقة البحثية إلى أن الجزائر لا تزال تعرف فراغا قانونيا كبيرا فيما يخص تنظيم قطاع الإشهار عموما وحماية الطفل من الإشهار التلفزيوني على وجه التحديد، سواء الطفل كمشارك في تقديم المضامين الإشهارية أو الطفل المتلقّي لها. Abstract: Television advertising is a powerful tool to influence the recipients of various advertising contents and messages and direct their behaviors, and the child is an important segment of society and is considered the focus of parents' purchasing decisions, a marketing target and an important part of the market due to the impact that television advertising has on his preferences and shaping his interests and behaviors. advertisers and owners of advertising institutions have resorted to exploiting this aspect to achieve commercial gains by using children in advertising campaigns without taking into account their privacy and their limited ability to evaluate the advertising content to which they are exposed or to which they participate in promoting. This raises many concerns about the legal nature of these practices. This study reviews the legal aspects related to this topic through a reading of the texts and regulations related to the advertising sector and media laws in Algeria, with the aim of revealing the legal protection guaranteed by Algerian legislation to the child from television advertising. This research paper concluded that Algeria still has a major legal vacuum regarding the regulation of the advertising sector in general and the protection of the child from television advertising in particular, whether the child as a participant in providing advertising contents or the child recipient of them.
Keywords: الإشهار التلفزيوني; التشريع الجزائري; Television advertising; Algerian legislation; exploitation; child protection